2010
DOI: 10.1152/ajpheart.01090.2009
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of A1adenosine receptors in altered vascular responses and inflammation in an allergic mouse model of asthma

Abstract: Poor lung function and respiratory disorders like asthma have a positive correlation with the development of adverse cardiovascular events. Increased adenosine levels are associated with lung inflammation that could lead to altered vascular responses and systemic inflammation. We hypothesized that asthmatic lung inflammation has systemic effects through A 1 adenosine receptors (A1AR) and investigated the effects of aerosolized adenosine on vascular reactivity and inflammation, using A1AR knockout (A1KO) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…CCR3 was predominantly expressed on macrophages and they suggest eotaxin may participate in mast cell activation or recruitment. In addition to this, in our most recent study [61] we have found significantly higher levels of IL-5 in aortic tissue of allergic A 1 WT mice. This may further support a role for IL-5 induced eotaxin effects in vasculature.…”
Section: Possible Pathway For Adenosine-induced Vascular Changes Isupporting
confidence: 65%
See 1 more Smart Citation
“…CCR3 was predominantly expressed on macrophages and they suggest eotaxin may participate in mast cell activation or recruitment. In addition to this, in our most recent study [61] we have found significantly higher levels of IL-5 in aortic tissue of allergic A 1 WT mice. This may further support a role for IL-5 induced eotaxin effects in vasculature.…”
Section: Possible Pathway For Adenosine-induced Vascular Changes Isupporting
confidence: 65%
“…Recent work from our lab [61] using A 1 AR knock-out (A 1 AR KO) mice has shown the involvement of A 1 ARs in systemic and vascular inflammation. Data showed that the allergic A 1 WT mice (A 1 WT SEN and A 1 WT SEN+AD groups) had lower adenosine-mediated aortic relaxation to 5’-N-ethylcarboxamidoadenosine (NECA; non-selective adenosine analog) (Table 2) and higher contraction to 2-chloro-N6-cyclopentyladenosine (CCPA; selective A 1 AR agonist), with increased protein expression of A 1 AR in the aorta.…”
Section: Adenosine Receptors In Asthma and Vasculaturementioning
confidence: 99%
“…In this model, mice were sensitized and challenged exclusively via the intranasal route, without the use of adjuvants. Unlike other published models , many of which sensitize by administration of ragweed plus adjuvant via the intraperitoneal route, we extended the sensitization period to 5 weeks of intranasal allergen exposure (5 days per week) to mimic as closely as possible the route and extent of sensitization in humans. Previous studies have shown that ragweed sensitization can be achieved by intranasal exposure in a shorter period of time if the environment is enriched with GM‐CSF or if multiple allergens are used in a chronic model.…”
Section: Discussionmentioning
confidence: 99%
“… Hua et al (2007) demonstrated that adenosine-induced bronchoconstriction in mice is mediated via the A 1 AR. Ponnoth et al (2010) demonstrated using allergic WT and A 1 AR KO mice that this receptor is systemically proinflammatory and increases airway hyperresponsiveness. Use of DNA antisense against the A 1 AR in a rabbit model of asthma suggested that receptor subtype may promote bronchoconstriction ( Nyce and Metzger, 1997 ).…”
Section: Roles Of Ars In Bronchoconstrictionmentioning
confidence: 99%